2017
DOI: 10.3390/batteries3030022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of C14- and C15-Predomiated AB2 Metal Hydride Alloys for Electrochemical Applications

Abstract: Abstract:Herein, we present a comparison of the electrochemical hydrogen-storage characteristics of two state-of-art Laves phase-based metal hydride alloys (Zr 21.5 (V and Cr) in the first composition results in an average electron density below the C14/C15 threshold ( e/a ∼ 6.9) and produces a C14-predominated structure, while the average electron density of the second composition is above the C14/C15 threshold and results in a C15-predominated structure. From a combination of variations in composition, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 100 publications
(116 reference statements)
1
13
0
Order By: Relevance
“…In the C-size cell, performances of AB 2 (between C14 and C15) [27], a Fe-free [28] and a Fe-doped [29] superlattice MH alloys were measured, and that results can be summarized as follows: C15-based MH alloy was more suitable for high-rate application comparing to those from C14 alloy and confirm previous half-cell results [16], superlattice alloy showed better high-rate and low-temperature performances comparing to those of AB 5 MH alloy, and Fe in the superlattice alloy can extend the cycle life by preventing Al-leaching from the negative electrode. In the newly developed pouch type cell, the high-capacity core-shell Ni(OH) 2 was compared to the conventional single-phase Ni(OH) 2 , and lower impedance and better charge retention were observed [30].…”
Section: Cell Performance Comparisonsupporting
confidence: 85%
See 1 more Smart Citation
“…In the C-size cell, performances of AB 2 (between C14 and C15) [27], a Fe-free [28] and a Fe-doped [29] superlattice MH alloys were measured, and that results can be summarized as follows: C15-based MH alloy was more suitable for high-rate application comparing to those from C14 alloy and confirm previous half-cell results [16], superlattice alloy showed better high-rate and low-temperature performances comparing to those of AB 5 MH alloy, and Fe in the superlattice alloy can extend the cycle life by preventing Al-leaching from the negative electrode. In the newly developed pouch type cell, the high-capacity core-shell Ni(OH) 2 was compared to the conventional single-phase Ni(OH) 2 , and lower impedance and better charge retention were observed [30].…”
Section: Cell Performance Comparisonsupporting
confidence: 85%
“…In the Laves phase-based AB 2 family, doping effects of Pd [14] and B [15] to a C14-predominated alloy were studied and a comparison between C14-and C15-MH alloys was also presented [16]. The preliminary conclusions are both Pd and a newly formed V 3 B 2 phase improve the surface catalytic ability and C15 alloy is more suitable for high-rate application.…”
Section: Metal Hydride Alloysmentioning
confidence: 99%
“…Stacking of the A2B4 slabs in the CeNi3, Nd2Ni7, and Sm5Ni19 phases is the same as that in the C14 crystal structure and is considered as the hexagonal group, and the rhombohedral group containing the NdNi3, Pr2Ni7, and Nd5Co19 phases shares the same A2B4 stacking as the C15 structure. The C14-and C15-based MH alloys behave differently in the EC environment, and we have reported the comparison previously [82] and concluded that the C14-predominated alloy is more suitable for high-capacity and long-cycle life applications, whereas the C15-predominated alloy is preferable in applications requiring easy activation and good high-rate and low-temperature …”
Section: Performance Correlation With Phase Structurementioning
confidence: 83%
“…Similar alloys with the same structure were also used in the first-generation Ni/MH batteries made by Gold Peak Industries (Hong Kong, China) and Hitachi-Maxwell (Osaka, Japan). Recently, the electrochemical performances of a state-of-art C14-predominate MH alloy were compared to those from a recently proposed C15-based MH alloy together with a review of the development works done on the C15-based MH alloys [27]. In this paper, we will review only research focused on the C14-predominated MH alloys.…”
Section: Introductionmentioning
confidence: 99%